Pelaksanaan Penertiban Gelandangan dan Pengemis Oleh Satuan Polisi Pamong Praja di Kota Denpasar - I Dw Md Suryawan Wira Kesuma; Ida Ayu Putu Widiati; Luh Putu Suryani (Jurnal Analogi Hukum, 2025)
Denpasar City, a popular tourist destination, is struggling to maintain peace and order due to rapid urbanization and an influx of migrants. This has led to an increasing number of job seekers exceeding the job opportunities available in the city. The problems in writing this thesis are (1) How is the implementation of the control of vagrants and beggars by the Pamong Praja Police Unit in Denpasar City? and (2) How are the obstacles faced by the Pamong Praja Police Unit in controlling vagrants and beggars in Denpasar City. The research method used is an empirical method by collecting data through interviews with related parties, document analysis, and direct observation of the curbing process. The results showed that the curbing and handling of vagrants and beggars in Denpasar City has not gone well, seen from the many activities of vagrants and beggars in Denpasar City so that it still disturbs public order. The obstacles of the Civil Service Police Unit in controlling vagrants and beggars are divided into Juridical and Non-Juridical obstacles. The Denpasar City Government is still trying to deal with the social problems of vagrants and beggars by means of preventive, refrensive, and rehabilitation.